Post disaster management for residential estates in Pasir Mas, Kelantan / Muhamad Nor Iqmal Nor Azli and Mohd Fadzil Mat Yassin - Nor Azli, Muhamad Nor Iqmal; Mat Yassin, Mohd Fadzil (2023)
This research study focuses on post-disaster management in urban areas, using flash floods as a case study. The research commences with an introduction outlining the research area’s background, problem statement, research questions, aims, and objectives, emphasizing its significance. The methodology section elaborates on the approach, incorporating literature review, questionnaire survey, and case study. The literature review explores natural and manmade disasters, delving into post-disaster management and reconstruction while analysing emergency responses and identifying research gaps. The research methodology further explains the chosen design, sampling techniques, data collection methods, and data analysis tools, utilizing Likert scales. Findings and discussions present survey results, including respondent demographics and questionnaire analysis, culminating in summarizing the study’s conclusions, successfully achieving the research objectives. The study culminates in recommendations for enhancing post-disaster management, considering factors affecting implementation among local authorities and communities. This research significantly contributes to comprehending and improving post-disaster strategies in urban areas impacted by flash floods.